1980
DOI: 10.3109/00016348009154090
|View full text |Cite
|
Sign up to set email alerts
|

Urethral pressure profile in continent women from childhood to old age

Abstract: One hundred and sixty-nine urinary continent females were examined with simultaneous urethro-cystometry, using a dual microtip-catheter. It was shown that the maximum urethral pressure and the urethral length increased from infancy to the age of 20--25 years. Thereafter, the values of these parameters decreased with increasing age. The bladder pressure remained constant in the different age groups. In six women, aged between 20 and 25 years, the parameters were measured three times during a menstrual cycle. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
55
1
6

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(80 citation statements)
references
References 10 publications
18
55
1
6
Order By: Relevance
“…We know that maximum urethral closure pressure decreases with age; however, this decrease becomes significant only after the age of 36 years, with a 2-4% decrease in function up to age 40 years. 17,18 In addition, correlation analysis of maximum urethral closure pressure on age revealed that age explained only 2.4% of the variation in the maximum urethral closure pressure. Linear regression also confirmed an independent effect of race on both the cotton-swab strain angle and the urethral closure pressure during a maximum pelvic muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…We know that maximum urethral closure pressure decreases with age; however, this decrease becomes significant only after the age of 36 years, with a 2-4% decrease in function up to age 40 years. 17,18 In addition, correlation analysis of maximum urethral closure pressure on age revealed that age explained only 2.4% of the variation in the maximum urethral closure pressure. Linear regression also confirmed an independent effect of race on both the cotton-swab strain angle and the urethral closure pressure during a maximum pelvic muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…When we look at the specifi c condition of stress incontinence, resting MUCP value is known to tend to be lower than in continent women and decreases as a function of age (11)(12)(13)(14)(15)(16), but there is no absolute cut-off value with suffi cient sensitivity and specifi city for that diagnosis and the association between MUCP and the severity of incontinence (1,21,22). In our population, MUCP values at rest (P1) tend to be lower in stress incontinent women except in the middle age group where women with mixed incontinence (which however implies a stress component) have lower MUCP.…”
Section: Discussionmentioning
confidence: 99%
“…The main criticism addressed to it is that it is not an absolute measure of the urethral pressure, since it is an evaluation of the sphincter at rest, that does not provide information about the bladder neck or proximal urethra, that can be variable due to involuntary muscular contractions (irritant effect of the catheter), that the pressure varies with size and type of catheter, rate of perfusion, bladder volume and patient position (4), and that there is a wide variation in MUCP among individuals of similar age (16).…”
Section: Discussionmentioning
confidence: 99%
“…Women were excluded for a history of recurrent urinary tract infections, genital anomalies, known neurological disease, claustrophobia, or implanted foreign bodies that would preclude MRI examination. Because age (13) and race (14) affect continence, controls were matched to cases for age and race. To accomplish this, as women were enrolled as cases, control women were recruited to provide the groups of similar age and race.…”
Section: Study Groupmentioning
confidence: 99%